DNA Measurement of Overlapping Cell Nuclei in Thick Tissue Sections - Liang Ji; James Tucker (Analytical Cellular Pathology)
The paper describes an improved image analysis procedure for measuring the DNA content of cell nuclei in thick sections of liver tissue by absorption densitometry. Whereas previous methods only permitted the analysis of isolated nuclei, the new technique enables both isolated and overlapping nuclei to be measured. A 3D segmentation procedure determines whether each object is an isolated nucleus or a pair of overlapping nuclei; in the latter case the combined optical density is redistributed to the individual nuclei. A selection procedure ensures that only complete nuclei are measured.